The impact of motivational factors, social sites,and affinity of Gen Y towards mobile phone purchase decision / Azrul Azwan Redzuan - Redzuan, Azrul Azwan (Faculty of Business and Management, UITM Sarawak, 2015)
The purpose of this study is to identify what are the factors impacting the customer purchase decision on mobile phone among Gen Y group in Kuching Sarawak. The determinants or factor of purchase decision among Gen Y group were discussed in this research are motivational factors, social sites and affinity of Gen Y towards mobile phone. The objective of this research is to identify the relationship between motivational factors that influence Gen Y purchase decision of mobile phone, to examine relationship between affinity factors of Gen Y towards mobile phone on their purchase decision, and to examine between social sites credibility that influence Gen Y on purchase decision of mobile phone. The survey involves of 200 respondents from Kuching area but the data that can be used is only 150. Data obtained using primary and secondary data. The data was analyzed using SPSS software to get frequency, reliability, correlation, and regression. The results are all independent variables have a relationship to the purchase decision among Gen Y group.